ANALISIS PENDISTRIBUSIAN LABA DALAM AKUNTANSI SYARIAH UNTUK MENCAPAI PRINSIP KEADILAN PADA PT. BANK PANIN DUBAI SYARIAH Tbk - Sahrullah Sahrullah; Wahyuni Wahyuni (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to determine the distribution of profits in Islamic accounting at the Panin Dubai Syariah Bank. This study uses a quantitative descriptive analysis method in which company data used are financial statements and an explanation of the desired data in this study is the 2016-2018 financial statements. The results showed that the didtribution of profits to companies that apply Islamic accounting has been distributed proportionally where the profits are nit only distributed to capital owners, but the distribution is also carried out to customers, employees, alms, and general reserves. Although for 2017-2018 there is no distribution of zakat. Implementation of the fair value of the distribution of profits has reached fair value in accordance with company policy rules. Although it has not been fully realized according to Islamic rules because the distribution of shareholders’ profit is greater than that of customers.